Phytochemical and bioactivity studies of zingiber amaricans blume - Abd Manaf, Ali; Riyanto, S.; Md., Sukari; Mohd., Aspollah (2011)
Phytochemical studies on the rhizomes of Zingiber amaricans afforded zerumbone 1 as the major constituent together with sterol mixtures containing stigmasterol 2. p-sitosterol cholesterol and campesterol E• The structures of the isolated compounds were elucidated using spectroscopic methods. The crude extracts and isolated pure compounds were examined for their bioactivity against phatogenic microbes and cancer cell lines. Zerumbone 1 shows moderate cytotoxic activity against human lymphoblastic T leukemia cell